Resources, Values, Identity: Young Cosmopolitans and the Referendum on British Membership of the European Union. Issue 1 (10th October 2018) - Ehsan, Rakib; Sloam, James
Abstract: In the aftermath of the global financial crisis, we have witnessed a resurgence in nationalism, Euroscepticism and populist politics in Europe and the United States. Young people have borne the brunt of this crisis. Yet, in the 2016 UK referendum, the vast majority of younger citizens voted for Britain to remain in the European Union. But why did they do so? Drawing upon a bespoke survey of 1351 18- to 30-year-olds, this article investigates the relative importance of socio-demographic factors, post-materialist values and primary self-identification. It finds that positive views about cultural diversity and being a full-time student were the greatest predictors of a young person voting Remain, whilst no significant association is found between higher educational attainment and voting Remain at the multivariate level. Setting the EU referendum within the broader context of youth politics, the article also identifies the existence of cosmopolitan values amongst young Remainers. This has major implications for both our understanding of the success of Jeremy Corbyn and the Labour Party amongst young voters in the 2017 general election, and the challenges the Conservative Party faces with regard to establishing support among Britain's young cosmopolitans for future elections.